ANALISIS PEMANFAATAN MEDIA DIGITAL PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS V - Oktavia Adinda; M. sobry; Silka Yuanti Draditaswari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Research on the utilization of digital media in elementary school learning, particularly in Indonesian language instruction, remains limited. This study aimed to identify: (1) the forms of digital media utilization in fifth-grade Indonesian language learning at SDN 2 Sigerongan, (2) the obstacles faced by teachers in utilizing digital media, and (3) the efforts made to overcome these obstacles. This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The research participants included the principal, the fifth-grade Indonesian language teacher, and fifth-grade students of SDN 2 Sigerongan. Data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that the utilization of digital media in fifth-grade Indonesian language learning at SDN 2 Sigerongan had not been implemented consistently in every stage of learning activities. In the preliminary stage, teachers used YouTube videos as an ice-breaking activity. In the main activity stage, Canva was utilized as a learning media under certain conditions. In the closing stage, Quizizz was used as an evaluation tool. The obstacles encountered included limited facilities such as smart TVs and LCD projectors, unstable internet access, and teachers’ limited skills in utilizing digital media. Efforts to overcome these obstacles included sharing facilities alternately, using teachers’ personal devices, and adjusting the use of digital media to classroom conditions. This study is expected to serve as a reference for teachers and schools in developing the use of digital media in Indonesian language learning at the elementary school level.